Evaluation of the economic performance of private pension systems in Latin America (1997-2008) - Duarte Ojeda, José Ricardo; Elizalde Sánchez, Carlos Cebarut; Casparri, María Teresa (Sociedad y Economía, 2011)
Pension systems in Latin America have experienced an unprecedented wave of reforms in the nineties; the pioneer is the case of Chile, which has migrated in 1981 from the solidarity sharing system (PAYGO) to individual capitalization system. It’s a contrasting change of neoliberal policy has privatized pensions for workers, causing a variety of results, this article analyzes the economic performance of 5 selected systems: Mexico, Argentina, Chile, Peru and Bolivia in a period where there have been many changes in financial outlook at continental and global level, which has affected the capital market and triggered one of the worst crisis of the reformed funds system in 2007-2008.